2016
DOI: 10.1155/2016/9238290
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances of the NLRP3 Inflammasome in Central Nervous System Disorders

Abstract: Inflammasomes are multiprotein complexes that trigger the activation of caspases-1 and subsequently the maturation of proinflammatory cytokines interleukin-1β and interleukin-18. These cytokines play a critical role in mediating inflammation and innate immunity response. Among various inflammasome complexes, the NLRP3 inflammasome is the best characterized, which has been demonstrated as a crucial role in various diseases. Here, we review recently described mechanisms that are involved in the activation and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
121
0
16

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(141 citation statements)
references
References 121 publications
4
121
0
16
Order By: Relevance
“…In addition to its hypoglycemic effects, glibenclamide has been shown to play a protective role in inflammation‐related disorders, particularly in CNS injury, including traumatic brain injury (Patel, Gerzanich, Geng, & Simard, ; Xu et al, ), ischemia‐reperfusion injury (Abdallah, Nassar, & Abd‐El‐Salam, ; Caffes et al, ; Gao et al, ; Yang et al, ), subarachnoid hemorrhage (SAH) (Simard et al, ; Tosun et al, ), and ICH (Jiang et al, ; Ma et al, ). Glibenclamide significantly attenuates neuroinflammation, decreases disruption of the BBB, and improves memory function by blocking the Sur1–Trpm4 channel in both experimental SAH and ICH (Zhou, Shi, Wang, Chen, & Zhang, ). Another study suggested that inhibiting microglial Sur1‐Trpm4 channels downregulates the transcription of inducible nitric oxide synthase, leading to reduced activation of microglia and an inflammatory response in the CNS (Kurland et al, ; Tosun et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its hypoglycemic effects, glibenclamide has been shown to play a protective role in inflammation‐related disorders, particularly in CNS injury, including traumatic brain injury (Patel, Gerzanich, Geng, & Simard, ; Xu et al, ), ischemia‐reperfusion injury (Abdallah, Nassar, & Abd‐El‐Salam, ; Caffes et al, ; Gao et al, ; Yang et al, ), subarachnoid hemorrhage (SAH) (Simard et al, ; Tosun et al, ), and ICH (Jiang et al, ; Ma et al, ). Glibenclamide significantly attenuates neuroinflammation, decreases disruption of the BBB, and improves memory function by blocking the Sur1–Trpm4 channel in both experimental SAH and ICH (Zhou, Shi, Wang, Chen, & Zhang, ). Another study suggested that inhibiting microglial Sur1‐Trpm4 channels downregulates the transcription of inducible nitric oxide synthase, leading to reduced activation of microglia and an inflammatory response in the CNS (Kurland et al, ; Tosun et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The sterile inflammatory reaction is important in the pathophysiology of ICH (Zhou et al, ). Thrombin and hemoglobin breakdown products after ICH can trigger a sterile inflammatory response through the NLRP3 inflammasome.…”
Section: Discussionmentioning
confidence: 99%
“…However, the NLRP3 inflammasome activation pathway has not yet been fully characterised. The role that calcium signalling, mitochondrial dysfunction, and destabilised lysosomes play in NLRP3 activation has not been fully elucidated (Zhou, Shi, Wang, Chen, & Zhang, 2016). There is a consensus that the canonical activation of the NLRP3 inflammasome requires two signals called "priming" (Signal 1) and "activation" (Signal 2) (Prochnicki, Mangan, & Latz, 2016).…”
Section: Nlrp3 Inflammasome Activation Pathwaymentioning
confidence: 99%
“…Moreover, IL-18 levels in young animals were slightly higher compared with aged. RT-PCR, reverse-transcription polymerase chain reaction NLRP3 components are induced during the first, priming signal through the toll-like receptor (TLR)-NF-κB pathway (Chang et al, 2015;Zhou, Shi, Wang, Chen, & Zhang, 2016). The subsequent assembly of NLRP3 inflammasome complex occurs during a second signal that can be triggered by several stimuli, both exogenous (including infection, tissue damage, and metabolic dysregulation) and endogenous (including the production of ROS, mitochondrial dysfunction, and accumulation of molecules such as extracellular ATP, hyaluronan, Aβ fibrils, and uric acid crystals; Chang et al, 2015;Walsh et al, 2014;Zhou et al, 2016).…”
Section: Real-time Rt-pcr Analysismentioning
confidence: 99%